Income Inequality and Poverty of Economies in Transition - Marina Popova (Luxembourg Income Study (LIS), 1996)
This paper compares income inequality in former socialist countries with those in a market society, focusing on the ways in which social welfare systems operate in different states. Evidence of inequality and poverty is considered for three countries: Russia; Poland; and Finland. These issues in Russia are considered both at the country level and for one region - the Republic of Karelia. A sensitivity analysis is also done on the techniques used to measure income inequality and poverty.
Keywords: 330; Armut; Einkommensverteilung; Übergangswirtschaft; Russland; Polen; Finnland; Karelien